International perspectives on knowledge integration : theory, research, and good practice in pre-service teacher and higher education - Lehmann, Thomas (Postdoctoral researcher) (Brill Sense, 2020)
"Interest in knowledge integration grew considerably in recent years, particularly within the realm of pre-service teacher education. However, studies on the topic conceptualize knowledge integration in diverse ways. For example, it may be conceived as a specific coherence-building learning process which involves not only acquiring but interrelating knowledge of different types (e.g., theoretical and practical) or from different domains, which together constitute a teacher's or educational specialist's professional knowledge base (e.g., content knowledge, pedagogical knowledge, pedagogical content knowledge, knowledge about using technologies for learning and instruction, etc.). Furthermore, knowledge integration also refers to the meaningful application of knowledge of different types and from various domains in order to act professionally and to teach successfully. In many countries, however, future teachers and educational specialists often struggle with knowledge integration, because the task of integrating knowledge across domains, from various courses, and from practical training is left largely to the individuals. Thus, the efficacy and quality of higher education programs, particularly in pre-service teacher education, could be improved through careful attention to knowledge integration. International Perspectives on Knowledge Integration aims at facilitating the consideration of knowledge integration in teacher training and higher education in both research and practice. Specifically, it explores theoretical conceptions and methods, and reports on original research and good practices for fostering knowledge integration. It is thus of interest to researchers, faculty board members, and lecturers concerned with teacher training and higher education, as well as to student-teachers and students of pedagogy, education, and educational psychology"--